2017
DOI: 10.1002/arch.21440
|View full text |Cite
|
Sign up to set email alerts
|

A gene‐driven recovery mechanism: Drosophila larvae increase feeding activity for post‐stress weight recovery

Abstract: Recovery from weight loss after stress is important for all organisms, although the recovery mechanisms are not fully understood. We are working to clarify these mechanisms. Here, we recorded enhanced feeding activity of Drosophila melanogaster larvae from 2 to 4 h after heat stress at 35°C for 1 h. During the post-stress period, expression levels of sweet taste gustatory receptor genes (Grs), Gr5a, Gr43a, Gr64a, and Gr64f, were elevated, whereas bitter taste Grs, Gr66a, and Gr33a, were decreased in expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, the anabolic process accompanying tissue repair also needs to be sustained by nutrient influx. Studies in Drosophila have shown that heat stress depletes energy stores and has a prolonged effect on metabolite profile and fly fitness (Klepsatel et al, 2016;Sarup et al, 2016;Ryuda et al, 2018). So far, however, the molecular mechanisms underlying nutrient supply during heat stress and tissue repair remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the anabolic process accompanying tissue repair also needs to be sustained by nutrient influx. Studies in Drosophila have shown that heat stress depletes energy stores and has a prolonged effect on metabolite profile and fly fitness (Klepsatel et al, 2016;Sarup et al, 2016;Ryuda et al, 2018). So far, however, the molecular mechanisms underlying nutrient supply during heat stress and tissue repair remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We recently investigated the effects of acute heat stress on feeding activities and body weights of Drosophila melanogaster larvae of the y w strain during the poststress period to test our hypothesis that animals possess systemic mechanisms to cope with and survive the damage caused by environmental stressors. 7 Feeding rates of Drosophila larvae were shown to decrease soon after the stress at 35°C for 1 hour, which caused reduction in body weight 2 hours after the stress. Thereafter, feeding activities increased to higher levels compared with control larvae at 3 hours after the heat stress.…”
mentioning
confidence: 98%